2001
DOI: 10.1037/0096-3445.130.4.681
|View full text |Cite
|
Sign up to set email alerts
|

Do threatening stimuli draw or hold visual attention in subclinical anxiety?

Abstract: Biases in information processing undoubtedly play an important role in the maintenance of emotion and emotional disorders. In an attentional cueing paradigm, threat words and angry faces had no advantage over positive or neutral words (or faces) in attracting attention to their own location, even for people who were highly state-anxious. In contrast, the presence of threatening cues (words and faces) had a strong impact on the disengagement of attention. When a threat cue was presented and a target subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

109
1,290
41
14

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,295 publications
(1,454 citation statements)
references
References 70 publications
(116 reference statements)
109
1,290
41
14
Order By: Relevance
“…This is consistent with the idea that involuntary attentional orienting toward cue-associated stimuli is an adaptive mechanism that allows the organism to rapidly orient its attentional resources toward the reward-related location, thereby increasing the possibility of obtaining rewards (Hickey et al, 2011). Nonetheless, this finding is different from several experiments investigating the role of initial orienting and difficulty of disengagement on the involuntary attentional orientation toward affectively negative relevant stimuli (e.g., Fox et al, 2001;Koster, Crombez, Verschuere, & De Houwer, 2004;Mogg, Holmes, Garner, & Bradley, 2008;Van Damme, Crombez, & Notebaert, 2008;Yiend & Mathews, 2001). These studies rather found more evidence for a difficulty of disengagement than for a rapid initial orienting.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with the idea that involuntary attentional orienting toward cue-associated stimuli is an adaptive mechanism that allows the organism to rapidly orient its attentional resources toward the reward-related location, thereby increasing the possibility of obtaining rewards (Hickey et al, 2011). Nonetheless, this finding is different from several experiments investigating the role of initial orienting and difficulty of disengagement on the involuntary attentional orientation toward affectively negative relevant stimuli (e.g., Fox et al, 2001;Koster, Crombez, Verschuere, & De Houwer, 2004;Mogg, Holmes, Garner, & Bradley, 2008;Van Damme, Crombez, & Notebaert, 2008;Yiend & Mathews, 2001). These studies rather found more evidence for a difficulty of disengagement than for a rapid initial orienting.…”
Section: Discussionsupporting
confidence: 80%
“…The spatial cuing task was adapted from other studies investigating attentional orienting toward emotional stimuli (e.g., Fox, Russo, Bowles, & Dutton, 2001;Vogt, De Hower, Koster, Van Damme, & Crombez, 2008). Each trial began with a fixation cross presented randomly for between 250 and 750 ms in the center of the screen with a white background.…”
Section: Spatial Cuing Taskmentioning
confidence: 99%
“…Literature on anxiety suggests that this inability to disengage from threat cues plays an important part in the maintenance of anxiety disorder (Fox et al, 2001); our findings suggest that this may also be the case for loneliness. For social anxiety, specifically, disengagement difficulties have been linked to rumination of negative social events, which encourages the activation of memories associated with negative social evaluation or negative social experiences (Buckner et al, 2010).…”
Section: Discussionsupporting
confidence: 60%
“…As noted previously, this may reflect a trade-off between initial attentional engagement and response latency. That is, initially directing more attention to one class of stimuli (i.e., angry expressions) may slow subsequent responses to other stimuli (i.e., happy expressions) due to difficulties in attentional disengagement from threatening faces (Koster et al, 2004;Fox et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, across both tasks, ERP responses indicative of greater attention to angry as compared to happy expressions were associated with relatively slower explicit categorization decisions to happy expressions. This pattern of results may reflect that participants for whom angry expressions attract more attention (as reflected in the N100 in the race task and the P200 in the emotion task) have difficulties in attentional disengagement from threatening faces (Koster, Crombez, Van Damme, Verschuere, & Houwer, 2004;Fox et al, 2001) that may later translate into slower responses to happy faces.…”
Section: Emotion Contrasts-mentioning
confidence: 99%